Are the Processes Underlying Discrimination the Same for Women and Men? A Critical Review of Congruity Models of Gender Discrimination - Manzi, Francesca (Frontiers in Psychology, 2019)
Although classic congruity models of gender discrimination (e.g., role congruity theory, lack of fit) predict negative outcomes for both women and men in gender-incongruent domains, the literature has focused almost exclusively on discrimination against women. A number of recent studies have begun to address the question of whether and under what circumstances men can also be the targets of gender discrimination. However, the results of these studies have so far been mixed. Therefore, the question of whether men, like women, also suffer discrimination when in gender incongruent roles and domains remains unclear. The goal of the present paper is to integrate and critically examine the burgeoning literature on gender discrimination against men in order to assess whether the symmetrical predictions of congruity models are supported. Through this close analysis and integration of the literature, I aim to identify remaining gaps in the research on gender discrimination. In particular, I propose that researchers of gender discrimination would benefit from expanding their scope beyond that of paid work.